2017
DOI: 10.1186/s12955-017-0753-2
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel disease-specific health-related quality of life instruments: a systematic review of measurement properties

Abstract: BackgroundThis review aims to critically appraise and compare the measurement properties of inflammatory bowel disease (IBD)-specific health-related quality of life instruments.MethodsMedline, EMBASE and ISI Web of Knowledge were searched from their inception to May 2016. IBD-specific instruments for patients with Crohn’s disease, ulcerative colitis or IBD were enrolled. The basic characteristics and domains of the instruments were collected. The methodological quality of measurement properties and measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
59
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 98 publications
0
59
0
3
Order By: Relevance
“…Several other inflammatory bowel disease-specific instruments for assessing QoL exist, evaluating physical, emotional, and social function in addition to symptom burden, but whether these are sufficiently valid and responsive for use as RCT endpoints remains unclear. 131 Other PROs assessing CD or ulcerative colitis (UC) disease activity have been developed but not yet incorporated as RCT endpoints and thus not captured in this review. de Jong et al 132 have recently identified 20 different PRO measures, which are categorized as those monitoring disease activity and those evaluating patient perspectives on disease control and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…Several other inflammatory bowel disease-specific instruments for assessing QoL exist, evaluating physical, emotional, and social function in addition to symptom burden, but whether these are sufficiently valid and responsive for use as RCT endpoints remains unclear. 131 Other PROs assessing CD or ulcerative colitis (UC) disease activity have been developed but not yet incorporated as RCT endpoints and thus not captured in this review. de Jong et al 132 have recently identified 20 different PRO measures, which are categorized as those monitoring disease activity and those evaluating patient perspectives on disease control and QoL.…”
Section: Discussionmentioning
confidence: 99%
“…The Inflammatory Bowel Disease Questionnaire (IBDQ) is the most widely used disease-specific instrument designed and recommended to assess HRQoL in patients with IBD [11,25]. It was initially developed by Guyatt et al in 1989 [26], and now has been translated into and cross-culturally adapted in several different language versions.…”
Section: Health Related Quality Of Lifementioning
confidence: 99%
“…To complement the disease activity indices, UC trials often include endpoints capturing change in patients' HRQoL, with the most frequently used instrument being the 32-item Inflammatory Bowel Disease Questionnaire (IBDQ-32). [7][8][9] The IBDQ-32 captures the patient's experience of IBD on 4 domains of functioning and well-being: bowel and systemic symptoms; and emotional and social function. 10 Reviews of the measurement properties of the IBDQ-32 have found evidence supporting its reliability, content validity, construct validity, and responsiveness.…”
Section: Reviewmentioning
confidence: 99%